Influence of Perceived Service Quality on Customer Loyalty - Madumere Humphrey Ikenna; Dickson Ben Uche; Agu Godswill Agu (Quantitative Economics and Management Studies, 2021)
The purpose of this was to investigate the relationship between perceived service quality and customer loyalty in the road transport industry in Nigeria. Leveraging the RATER service quality model, only reliability, tangibles and responsiveness were explored. Participants were drawn from the customer base of organized road transport firms operating in the South East of Nigeria. Being a quantitative survey, results from 318 valid responses were analyzed with SPSS version 21. Findings indicate that the three constructs (reliability, tangibles, and responsiveness) are significant predictors of customer loyalty, with reliability having the greatest influence, followed by responsiveness and tangibles. The study recommends steady monitoring of service quality as a step towards customer loyalty in the highly competitive road transport industry in Nigeria.